Effectiveness of Sex Pheromone in Controlling Cocoa Pod Borer, Conopomorpha cramerella (Snell.) - Endang Sulistyowati (Indonesian Coffee and Cocoa Research Institute, 2014)
Cocoa pod borer (CPB, Conopomorpha cramerella nell.) is a dangerous pest of cocoa which seriously reduce cocoa production mainly in Southeast Asia and Pasific. Prevention of CPB attack can be done by pod sleeving to prevent CPBs lay eggs on pod, or reduction of source of CPB infestation by using pheromone or kairomone as attractant in an insect trap. A preliminary research using sex pheromone has been conducted at endemic cocoa area infested by CPB in East Java. The objective of this study was to evaluate the effectiveness of sex pheromonesin controlling CPB. Trial was arranged by randomized completely block design in four treatments and four blocks as replication. Four densities trap/ha (0, 4, 8, and 12 traps/ha) were used as a treatments. Sex pheromone trap consisted of synthetic pheromone (lure) and sticky liner was hanged on 0.5 m above the cocoa canopy. The results showed that the number of CPB captured during four months was significantly decreased. The number of CPB captured per trap during the first two months in the treatment of 0, 4, 8 and 12 traps/ha were 0, 6.5, 4.72, and 5.58 CPBs, respectively. Four months after treatment, the number of CPB captured in the respective treatments was reduced to 0, 0.25, 0.6, and 0.96 CPBs. Estimate calculation on yield loss due to CPB attack showed that before treatment the yield loss ranged 37.4—45.6%, however six months after treatment, the yield loss in treatment plots decreased to 9.4—21%, whereas on control 38.47%. Use of sex pheromones to attract CPB at a density of 4 traps/ha reduced yield losses due to CPB damage by 67.7%. The significant correlation betweenthe number of CPB captured with the damage intensity followed regression equation of Y = - 0,00044X + 0,32059. Use of sex pheromone for monitoring or masstrapping of CPB, as a component in IPM of CPB is promising, due to its nature for specific target, environmentally friendly, effectiveness, and economic values.Key words: cocoa, cocoa pod borer, Conopomorpha cramerella, integrated pest management, biological control, sex pheromone